The positive allosteric modulator of NMDA receptors, GNE‐9278, blocks the ethanol‐induced decrease of excitability in developing retrosplenial cortex neurons from mice - Clark W. Bird; Carlos F. Valenzuela (Wiley, 2023)
Abstract Binge‐like exposure to ethanol during the brain growth spurt triggers apoptotic neurodegeneration in multiple brain regions, including the retrosplenial cortex, a brain region that is part of the hippocampal‐diencephalic‐cingulate memory network. This is mediated, in part, by reduced Ca2+ influx through N‐methyl‐d‐aspartate (NMDA) receptors followed by a decrease in the activation of pro‐survival genes. Here, we tested whether a positive allosteric modulator of NMDA receptors could counteract the inhibitory effect of ethanol on developing retrosplenial cortex pyramidal neurons. We used patch‐clamp electrophysiological techniques in acute slices from postnatal day 6-8 mice to test the effect of the positive allosteric modulator GNE‐9278 on ethanol‐induced inhibition of NMDA receptor function. GNE‐9278 dose‐dependently increased the amplitude, decay time, and total charge of NMDA excitatory postsynaptic currents. At a concentration of 5 μmol L−1, GNE‐9278 significantly reduced the 90 mmol L−1 ethanol‐induced inhibition of NMDA excitatory postsynaptic current amplitude, decay time, and total charge. Current‐clamp experiments showed that 5 μmol L−1 GNE‐9278 ameliorated the 90 mmol L−1 ethanol‐induced inhibition of synaptically‐evoked action potential firing and compound excitatory postsynaptic potential amplitude. These findings indicate that positive allosteric modulators mitigate ethanol‐induced hypofunction of NMDA receptors in developing cerebral cortex neurons, an effect that could ameliorate its pro‐apoptotic effects during the late stages of fetal development.